2017
DOI: 10.1186/s12891-017-1752-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor-1 deficiency enhances subchondral osteopenia after induction of osteoarthritis in mice

Abstract: BackgroundSubchondral osteopenia is important for the pathophysiology of osteoarthritis (OA). Although previous studies suggest that plasminogen activator inhibitor-1 (PAI-1), an inhibitor of fibrinolysis, is related to bone metabolism, its role in OA remains unknown. We therefore investigated the roles of PAI-1 in the subchondral bone in OA model mice.MethodsWild type (WT) and PAI-1-deficient (KO) mice were ovariectomized (OVX), and then destabilization of the medial meniscus (DMM) surgery was performed.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…In the future, the use of such mice could inform studies investigating the effect of Serpina1 deficiency in murine experimental arthritis. Fortunately, for most serpins, one human gene is mirrored with a single orthologue in rodents, and indeed transgenic animals have begun to be used successfully to understand the importance of these serpin genes in diseases, including OA [ 61 , 67 , 74 ].…”
Section: Discussion: Opportunities Challenges and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, the use of such mice could inform studies investigating the effect of Serpina1 deficiency in murine experimental arthritis. Fortunately, for most serpins, one human gene is mirrored with a single orthologue in rodents, and indeed transgenic animals have begun to be used successfully to understand the importance of these serpin genes in diseases, including OA [ 61 , 67 , 74 ].…”
Section: Discussion: Opportunities Challenges and Future Directionsmentioning
confidence: 99%
“…Interestingly, an inverse observation has been made for SerpinE1, as murine chondrocytes from SerpinE1 −/− mice show a reduction in IL-1 induced Mmp13 expression [ 60 ]. These mice also display accelerated subchondral osteopenia compared with wild-type mice following surgical induction of OA in ovariectomized female mice [ 61 ].…”
Section: Serpins In Cartilage and Osteoarthritismentioning
confidence: 99%
“…It is related to bone metabolism. Although it has been shown that PAI-1 deficiency accelerates subchondral osteopenia after induction of OA in mice, its role in OA remain unclear (Moritake et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…PAI‐1 deficiency has been reported in a patient with OI and spontaneous intraparenchymal haemorrhage (Goddeau et al , ). There is evidence that PAI‐1 also has a role in bone formation in mouse models (Mao et al , ; Moritake et al , ; Jin et al , ). PAI‐1 is stabilized by vitronectin which is anchored to collagen type 1 (Schvartz et al , ).…”
Section: Discussionmentioning
confidence: 99%